New insights into HIV/AIDS for students and healthcare professionals - Asekun-Olarinmoye, Esther Olufunmilayo; Alebiosu, Olutayo Christopher (Cambridge Scholars Publishing, 2019)
Since the first case of HIV was diagnosed in 1981, several efforts have gone into its prevention and control. However, it remains a leading scourge today, with no cure despite the international attention and publicity it receives. It is one of the few diseases specifically given attention in the Millennium Development Goals (MDG) and the Sustainable Development Goals (SDGs). There has been inadequate effort by academia in developing countries towards contributing to in-depth knowledge of HIV, as well as stimulating the interest of students in the topic. As the search for a cure continues, this.